Federal Policy in Educational Research and Development. Occasional Paper No. 5 - Clark, David L.; Ohio State Univ., Columbus. Center for Vocational and Technical Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
In 1867, a bill was passed by Congress establishing a department of education. The appropriations for the department were reduced almost immediately, and the status of the agency was undercut by reassigning it as an office in the Department of Interior. From 1867 to 1954, the United States Office of Education (USOE) and the federal government were bystanders in the field of educational research. The first breakthrough in federal policy toward educational research and development (R and D) came with the passage of the Cooperative Research Act in 1954. This Act authorized the commissioner of education to enter into "contracts or jointly financed cooperative arrangements with universities and colleges and state educational agencies for the conduct of research, surveys, and demonstrations in the field of education." In 1965, a second major breakthrough in educational R and D occurred with the passage of the Elementary and Secondary Education Act. The new programs brought about by the Act typified the expansionist mood of the 1960's. It was within this mood that the National Institute of Education (NIE) was established to coordinate the government's investment in R and D. Today the policy of the federal government is more comprehensive, vigorous, and supportive than any previous policy or combination of policies have been. However, there is considerable doubt about and dissatisfaction with the federal dollar investment in educational R and D in both the executive and legislative branches of the government. (Lecture questions and answers are included.) (RC)
Availability: Center for Vocational Education, Ohio State University, Columbus, Ohio 43210 (No price quoted).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Development; Educational Legislation; Educational Policy; Educational Research; Federal Government; Federal Legislation; Financial Policy; Speeches/Meeting Papers